Cloning, functional analysis, and transcriptional regulation of the Bacillus subtilis araE gene involved in L-arabinose utilization. - Sá-Nogueira, I (1997)
The Bacillus subtilis araR locus (mapped at about 294 degrees on the genetic map) comprises two open reading frames with divergently arranged promoters, the regulatory gene, araR, encoding a repressor, and a partially cloned gene, termed araE by analogy to the Escherichia coli L-arabinose permease gene. Here, we report the cloning and sequencing of the entire araE gene encoding a 50.4-kDa polypeptide. The araE gene is monocistronic (as determined by Northern blot analysis), and its putative product is very similar to a number of prokaryotic proton-linked monosaccharide transporters (the group I family of membrane transport proteins). Insertional inactivation of the araE gene leads to a conditional Ara- phenotype dependent on the concentration of L-arabinose in the medium. Therefore, we assume that araE encodes a permease involved in L-arabinose transport into the cell. The araE promoter region contains -10 and -35 regions (as determined by primer extension analysis) very similar to those recognized by RNA polymerase containing the major vegetative-cell sigma factor sigmaA, and the -35 region of the transcription start point for araE is located 2 bp from the -35 region of the araR gene. Transcriptional studies demonstrated that the expression from the araE promoter is induced by L-arabinose, repressed by glucose, and negatively regulated by AraR. These observations are consistent with a model according to which in the absence of L-arabinose, AraR binds to a site(s) within the araE/araR promoter, preventing transcription from the araE promoter and simultaneously limiting the frequency of initiation from its own promoter; the addition of L-arabinose will allow transcription from the araE promoter and increase the frequency of initiation from the araR promoter.